You need to change the signs of the terms if you move them from the left side to the right side, such that:

`y + 4x = 6 => y = -4x + 6`

You should notice that the term `4x` was moved from the left, where it has positive sign, to the right, with negative sign.

The steps you need to perform when you need to move one term from one side to the other, are:

`y + 4x = 6 => y + 4x - 4x = 6 - 4x` (subtract` 4x` from both sides to eliminate `4x` from the left, but to preserve the equation)

`y = 6 - 4x` (reduce duplicate terms form the left side)

`y = -4x + 6` (re-arrange the terms)

**Hence, evaluating the gradient and y intercept of the function `y + 4x = 6` yields `m = -4` (gradient), `b = 6` (y intercept).**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.